2020
DOI: 10.1002/cbf.3549
|View full text |Cite
|
Sign up to set email alerts
|

DMBT1 suppresses cell proliferation, migration and invasion in ovarian cancer and enhances sensitivity to cisplatin through galectin‐3/PI3k/Akt pathway

Abstract: Ovarian cancer (OC) is one of the most common gynaecologic malignancies. Deleted in malignant brain tumors 1 (DMBT1) was considered as a tumour suppressor in multiple cancers, but there have been no systemic profiling studies of DMBT1 in OC until now. The aim of this study is to explore the role and the potential mechanism of DMBT1 in OC. mRNA levels and protein expressions of corresponding genes were detected by quantitative real‐time polymerase chain reaction and western blot. Cell proliferation was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“… 48 , 49 , 50 Deleted in malignant brain tumors 1 (DMBT1) overexpression induced the inactivation of PI3K/AKT pathway, thereby suppressing cisplatin resistance in OC. 51 Wogonin enhanced cisplatin sensitivity in OC by inhibition of PI3K/AKT pathway. 52 As for the correlation between RHPN1‐AS1 and PI3K/AKT pathway, only one article reported that RHPN1‐AS1 could activate PI3K/AKT pathway to promote the malignancy of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“… 48 , 49 , 50 Deleted in malignant brain tumors 1 (DMBT1) overexpression induced the inactivation of PI3K/AKT pathway, thereby suppressing cisplatin resistance in OC. 51 Wogonin enhanced cisplatin sensitivity in OC by inhibition of PI3K/AKT pathway. 52 As for the correlation between RHPN1‐AS1 and PI3K/AKT pathway, only one article reported that RHPN1‐AS1 could activate PI3K/AKT pathway to promote the malignancy of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…The DMBT1 gene encodes a protein involved in cell proliferation and is considered a tumor suppressor for the brain and epithelial cancer [ 82 85 ]. Some studies have shown conflicting results in reducing or increasing the expression of DMBT1 in various cancers [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research have claimed that most proteins require interacting with other proteins in the cell to function properly, and this interaction between proteins may influence each other and form a complex regulatory network, thus exerting important effects on the biological processes of various kinds of tumor cells [ 24 , 25 ]. For example, Ma N et al demonstrated that deleted in malignant brain tumors 1 (DMBT1) could interact with galectin-3 and exert suppressive effects on cell proliferation, migration and invasion in ovarian cancer cells through galectin-3-mediated PI3k/Akt signaling [ 26 ]. Cui H et al confirmed the interaction between DTL and programmed cell death 4 (PDCD4) by Co-IP assay, and revealed that DTL enhanced the motility and proliferation of cancer cells through degrading PDCD4, thus promoting cancer progression [ 27 ].…”
Section: Discussionmentioning
confidence: 99%